2012
DOI: 10.1091/mbc.e12-05-0357
|View full text |Cite
|
Sign up to set email alerts
|

The CSC connects three major axonemal complexes involved in dynein regulation

Abstract: This study reveals the 3D structure of the CSC and its connections to three major axonemal complexes involved in dynein regulation, including the distal radial spoke and the nexin-DRC. The findings corroborate radial spoke heterogeneity and suggest a unique role for the distal spoke in calcium-mediated signal transduction and flagellar motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 67 publications
5
110
1
Order By: Relevance
“…mia mutants, albeit containing all I1 components, are slow swimmers deficient in phototaxis as I1 mutants (see the section Chemical Signaling for a detailed discussion). RS2 and RS3/RS3S are, respectively, adjacent to the front and back of the nexindynein regulatory complex (N-DRC) and perhaps the calmodulin-and spoke-associated complex (CSC) Dymek and Smith 2007;Heuser et al 2009Heuser et al , 2012Urbanska et al 2015). This arrangement is consistent with distinct inner dynein anomalies in mia mutants (King and Dutcher 1997) and N-DRC mutants (Piperno et al 1992).…”
Section: Morphology and Periodicity Of Radial Spokessupporting
confidence: 56%
See 1 more Smart Citation
“…mia mutants, albeit containing all I1 components, are slow swimmers deficient in phototaxis as I1 mutants (see the section Chemical Signaling for a detailed discussion). RS2 and RS3/RS3S are, respectively, adjacent to the front and back of the nexindynein regulatory complex (N-DRC) and perhaps the calmodulin-and spoke-associated complex (CSC) Dymek and Smith 2007;Heuser et al 2009Heuser et al , 2012Urbanska et al 2015). This arrangement is consistent with distinct inner dynein anomalies in mia mutants (King and Dutcher 1997) and N-DRC mutants (Piperno et al 1992).…”
Section: Morphology and Periodicity Of Radial Spokessupporting
confidence: 56%
“…Instead, they were identified in the pull-down of the anticalmodulin antibody. Knockdown of CSC proteins impaired RS2, RS3S, N-DRC, and a single-headed dynein, e (Dymek et al 2011;Heuser et al 2012), suggesting that the CSC is among the base of RS2 and RS3, N-DRC, and the nearby dynein. Consistent with this, the antibody for a CSC protein inhibits microtubule sliding velocity as the reduced microtubule sliding velocity of pf14 axonemes.…”
Section: Rs Outer Doublet Connectionsmentioning
confidence: 99%
“…Targets of Ca 2ϩ are not well understood, but pioneering studies in Chlamydomonas recently identified three axonemal protein complexes that bind calmodulin and are predicted to function in Ca 2ϩ regulation (82)(83)(84). The Chlamydomonas CMF22 orthologue, FAP82, was identified in the flagellar proteome (85) but was not identified as part of calmodulin-binding complexes in Chlamydomonas (86). Nonetheless, Ca 2ϩ -regulated motility is conserved in another trypanosome species, Crithidia oncopelti, where the direction of flagellar wave propagation is regulated by the concentration of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of Chlamydomonas mutants has also revealed conserved axonemal components that transmit signals from the central pair and radial spoke structures to the dynein motors. Most notable are the calmodulin and spoke associated complex (CSC; Dymek et al 2011, Heuser et al 2012a) and the DRC; see the next section for insights from recent cryoelectron tomography (cryo-ET) analyses of the axoneme (for reviews, see Heuser et al 2009, Porter 2012) and of the Mia-I1 dynein complex (Yamamoto et al 2013). The CSC and the DRC play roles in the control of the dynein motors: They are both ideally located to link the radial spokes to the outer doublets and the dynein motors.…”
Section: And Lindemann and Lesich (2010)mentioning
confidence: 99%
“…The notable features in figure 4 include a definition of the longitudinal 96-nm axonemal repeat (figure 4 D and E), which is probably the basic unit of activity along the axoneme and the substructure of the outer dynein arms, including the resolution of the globular motor domains ( figure 4d-4g). Also illustrated are the locations and substructure of each inner dynein arm (I1/f dynein and dyneins a-g; Bui et al 2012, Heuser et al 2012b, Lin et al 2014, the N-DRC (Heuser et al 2009), the CSC (Dymek et al 2011, Heuser et al 2012a, and the radial spokes (Pigino et al 2011, Barber et al 2012, Oda et al 2014). In addition, cryo-ET has revealed the substructure of the central pair apparatus (Carbajal-Gonzalez et al 2013, Oda et al 2014).…”
Section: And Lindemann and Lesich (2010)mentioning
confidence: 99%